The identification of chronic liver disease in primary care using non-invasive diagnostics within a novel pathway - Harman, David J. (2017)
Introduction: Deaths due to chronic liver disease have increased significantly in recent decades. This is due to increases in alcohol consumption and obesity during this time period, and insensitive screening tests (liver function blood tests) utilised in primary care. This thesis describes a new liver disease community diagnostic pathway which focussed upon defined risk factors for chronic liver disease and uses Transient Elastography (TE) as the primary investigation modality. The aims of the thesis are to assess the feasibility of this pathway for detecting liver disease due to alcohol or non-alcoholic fatty liver disease within the United Kingdom healthcare system, to quantify the number of new cases detected with this approach and to evaluate patient experience of these investigations.